ANALISIS FILM NANTI KITA CERITA TENTANG HARI INI - Melati Kusuma Wardhani, S.I.Kom, M.I.Kom, Melati Kusuma Wardhani, S.I.Kom, M.I.Kom (Akademi Komunikasi SAE Indonesia, 2023)
The film industry is booming right now, especially in Indonesia. As a means of entertainment and conveying messages to the public, various cinema themes have been produced. This study aims to qualitatively analyze the content (content analysis) in the exposure of the film